Comparative analysis of postendodontic pain using multiple versus single rotary file systems in single-visit endodontics: A randomized clinical trial - Nishtha K Patel; Kailas Attur; Kamal P Bagda; Krushnangi Yagnik; Prerak Doshi; Anjali Oak (Wolters Kluwer Medknow Publications, 2023)
Aim: The aim of this study was to compare and evaluate the severity of PEP using ProTaper Gold (PTG), ProTaper Next (PTN), and F-One rotary files in single-visit endodontic (SVE) treatment. Materials and Methods: In a randomized factorial clinical trial, 150 patients indicated for endodontic treatment in maxillary molars and mandibular molars were selected. They were separated into three groups: Group 1 (PTG), Group 2 (PTN), and Group 3 (F-One). SVE treatment was done under local anesthesia. The intensity of PEP was assessed using the Visual Analog Scale (VAS) after 24, 48, 72 h, and 1 week. Finally, the data were tabulated and statistically analyzed using SPSS software. VAS was analyzed using analysis of variance test with Scheffe's post hoc test. Results: PEP was less in Group 3 (F-One) and Group 2 (PTN) as compared to Group 1 (PTG) at 24.48 h which is statistically significant (P < 0.05), whereas the difference between PTN and F-One was statistically insignificant. Conclusion: All file systems showed PEP, but the intensity of pain was minimum in F-One single rotary file system followed by PTN and PTG Multi-file systems.